E>fTRY OF THE SMALL-SIZED MACKEREL, RASTRELLIGER KANAGURTA (CUVIER) INTO THE COCHIN BACKWATER DURING THE MONSOON SEASON - Noble, A (Indian Journal of Fisheries, 2011)
The Indian mackerel has already been reported to enter the rivers (Pradhan, 1956 and George et at., 1959) and backwaters (George, 1965) during January-May. However, their entry into these areas during the rainy season especidly when the salinity is low has not been reported earlier